2012
DOI: 10.1155/2012/507894
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Fetal HemoglobinIn VivoMediated by a Syntheticγ-Globin Zinc Finger Activator

Abstract: Sickle cell disease (SCD) and β-thalassemia patients are phenotypically normal if they carry compensatory hereditary persistence of fetal hemoglobin (HPFH) mutations that result in increased levels of fetal hemoglobin (HbF, γ-globin chains) in adulthood. Thus, research has focused on manipulating the reactivation of γ-globin gene expression during adult definitive erythropoiesis as the most promising therapy to treat these hemoglobinopathies. Artificial transcription factors (ATFs) are synthetic proteins desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Overexpression of endogenous γ‐globin has been induced in CD34+ cells from thalassemia patients with the use of lentiviral vectors expressing a zinc finger protein (GG1‐VP64) which interacts with the promoter of γ‐globin gene . Silencing of γ‐globin repressors, such as BCL11A, with lentiviruses carrying sequences of microRNAs has been shown to increase HbF production .…”
Section: New Therapeutic Approaches In Preclinical Development For β‐mentioning
confidence: 99%
“…Overexpression of endogenous γ‐globin has been induced in CD34+ cells from thalassemia patients with the use of lentiviral vectors expressing a zinc finger protein (GG1‐VP64) which interacts with the promoter of γ‐globin gene . Silencing of γ‐globin repressors, such as BCL11A, with lentiviruses carrying sequences of microRNAs has been shown to increase HbF production .…”
Section: New Therapeutic Approaches In Preclinical Development For β‐mentioning
confidence: 99%
“…Importantly, our results contribute to demonstrate that artificial zinc finger transcription factors may be a class of therapeutic reagents for treatment of crucial inherited diseases [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Gg1-VP64 was then tested in early erythroid progenitors derived from cytokine-mobilized adult peripheral blood CD34 + cells and this artificial transcription factor was able to increase HbF levels from 2% to 20% of the total hemoglobin which can be therapeutically applicable (Wilber et al 2010). Costa et al further showed 5-fold induction of HbF in gg1-VP64 β-YAC double-transgenic (bigenic) mice, demonstrating its efficacy in vivo (Costa et al 2012). …”
Section: Genome Editing To Induce Fetal Hemoglobin Expressionmentioning
confidence: 99%